O ensino pós-pandemia: os reflexos das dificuldades na aprendizagem da matemática no sistema de organização modular de ensino (SOME) no interior de Abaetetuba - PIMENTEL, John Elvis Silva (2024)
The impacts of the Covid-19 pandemic on basic education were significant, representing complex consequences that have not yet been fully assessed. Thus, the aim of this article is to examine the effects of the crisis on the teaching and learning process of Mathematics among the riverside people of the Rio Maracapucu Médio, an island in the Municipality of Abaetetuba, during and post-pandemic. The focus of this study was on students from the Modular Organization of Education System (SOME) at Tomaz Lourenço Negrão School. The goal was to analyze, from the perspective of these students, the impacts of the pandemic on the teaching and learning process and the challenges faced in the post-pandemic period. The methodology employed included qualitative, documentary, bibliographic approaches, and the application of questionnaires. The results revealed a significant decline in the teaching and learning process of these students, exacerbated by the lack of technological readiness of the school to support students, resulting in the inefficiency in knowledge absorption throughout this period until the present moment.